Application of carbon-fiber-reinforced polymer anode in electrochemical chloride extraction of steel-reinforced concrete. (1st September 2016) - Zhu, Ji-Hua; Wei, Liangliang; Wang, Zhaohua; Liang, Cheng Ke; Fang, Yuan; Xing, Feng
Highlights: Chloride was extracted from steel-reinforced concrete via electrochemical chloride extraction (ECE). Carbon-fiber-reinforced polymer (CFRP) served as external anode. Steel–concrete bond loss varied with samples' water–cement ratio and applied current density. CFRP anode performance showed no significant degradation after ECE treatment. ECE efficiency was compatible with that shown using activated titanium mesh anode. Abstract: A carbon-fiber-reinforced polymer (CFRP) was adopted as an external anode in the electrochemical chloride extraction (ECE) of cylindrical steel-reinforced concrete samples with different water–cement ratios and chloride introduced during casting. Three constant current densities were applied between the steel cathode and CFRP anode, with the internal steel bar used as the cathode. The chloride extraction ratio, proportion of residual chloride, and Cl − /OH − ratio were obtained to assess the ECE efficiency; pullout tests were conducted to evaluate the post-ECE bonding characteristics between steel and concrete. A microscopic evaluation of both concrete and CFRP showed that the CFRP anode did not experience severe degradation after ECE. Comparison of the performance by using activated titanium mesh anodes confirmed the feasibility of ECE with an external CFRP anode.